1991
DOI: 10.1007/bf00016077
|View full text |Cite
|
Sign up to set email alerts
|

Separate signal pathways regulate the expression of a low-temperature-induced gene in Arabidopsis thaliana (L.) Heynh.

Abstract: A cDNA clone corresponding to a novel low-temperature-induced Arabidopsis thaliana gene, named lti140, was employed for studies of the environmental signals and the signal pathways involved in cold-induced gene expression. The single-copy lti140 gene encodes a 140 kDa cold acclimation-related polypeptide. The lti140 mRNA accumulates rapidly in both leaves and roots when plants are subject to low temperature or water stress or are treated with the plant hormone abscisic acid (ABA), but not by heat-shock treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
167
2

Year Published

1993
1993
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(181 citation statements)
references
References 39 publications
11
167
2
Order By: Relevance
“…In RC12B mRNA it seems that both the ABA-dependent and -independent pathways are required to achieve full cold-induced accumulation. In conclusion, RC12 genes are induced by low temperature in abil and aba2 mutants, indicating that, as described for other cold-responsive genes (Nordin et al, 1991;Gilmour and Thomashow, 1991), the accumulation of RCT2 mRNAs by low temperature is regulated by at least two different signal transduction pathways, one ABA dependent and the other ABA independent.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…In RC12B mRNA it seems that both the ABA-dependent and -independent pathways are required to achieve full cold-induced accumulation. In conclusion, RC12 genes are induced by low temperature in abil and aba2 mutants, indicating that, as described for other cold-responsive genes (Nordin et al, 1991;Gilmour and Thomashow, 1991), the accumulation of RCT2 mRNAs by low temperature is regulated by at least two different signal transduction pathways, one ABA dependent and the other ABA independent.…”
Section: Discussionmentioning
confidence: 53%
“…Their high degree of homology suggests that they probably arose by duplication of the same ancestral gene. The same origin has been proposed for four pairs of Arabidopsis low-temperature-responsive genes, in which the homologous genes are arranged in tandem in the genome; they are kinl and cor6.6/kin2 (Gilmour et al, 1992;Kurkela and Borg-Franck, 1992), corl5a and corl5b (Wilhelm and Thomashow, 1993), W78/rd29A/cor78 and W65/rd29B (Nordin et al, 1991;Horvath et al, 1993;Yamaguchi-Shinozaki and Shinozaki, 1993), and Iti45/lti29 and cor47 . It is interesting that in each case both homologous genes have diverged in their regulation by low temperature, suggesting they have different roles in cold acclimation or freezing tolerance.…”
Section: Discussionmentioning
confidence: 60%
“…It is not yet fully understood how plants can sense osmotic stress, but it is clear that abscisic acid (ABA) is involved in the expression of a number of stress-responsive genes [4]. However, studies conducted on ABA-deficient or ABA-insensitive mutants have indicated that some of these genes are expressed independently of ABA [5,6]. With regard to anoxia, it is known to quickly inhibit protein synthesis, except for a selected set of proteins called anaerobic proteins (' ANPs ') ; most of them are enzymes of glycolysis and fermentation [2].…”
Section: Introductionmentioning
confidence: 99%
“…9 and 10). However, studies employing the ABA-insensitive (abi) mutants of Arabidopsis indicate that there are also ABA-independent signal transduction pathways for cold-and dehydration-regulated gene expression (11,12). Indeed, the results of Yamaguchi-Shinozaki and Shinozaki (6) indicate that the C-repeat͞DRE is not responsive to ABA levels and, thus, appears to impart cold-and dehydration-regulated gene expression through an ABAindependent pathway.…”
mentioning
confidence: 99%